Prospects for the development of Private banking in Russian commercial banks - E. E. Frolova (Путеводитель предпринимателя)
The article deals with topical issues of application in the sphere of banking services of such type of services as Private banking. In the list of systemically significant credit institutions approved by the Bank of Russia, which account for more than 60% of the total assets of the Russian banking sector, their number at the moment is only 11 banks. These banks offer Private banking services, the list and prospects of which are discussed in the article.